Pros and Cons of Riba Interest - Izza, Nadia Nurul; Al-Ayubi, Solahuddin (Islamic Economics Methodology, 2023)
This study aims to ascertain attitudes concerning usury interest throughout the previous 29 years, from 1994 to 2022. This study employs a qualitative analysis method on secondary data in the form of metadata from 146 publications indexed by Scopus, which was then processed using SentiStrength and Microsoft Excel 2019. According to the sentiment analysis's findings, there is a significant amount 49,3% of neutral sentiment followed by 32,2% of negative sentiment and 18,5% positive sentiment in expert opinions on usury interest. The study's findings revealed that the tendency of usury interest in Islamic banking is still on the rise. According to the study, many different types of usury practices exist. Thus, practitioners, academia, and the government must continue educating and socializing people about usury-free economic methods that adhere to Islamic principles. These findings can be used as an example to educate the general public and society about usury interest and Islamic finance and economics.